Fighting words - Bradley, Kimberly Brubaker (Dial Books for Young Readers, 2020)
Depending on an older sister who protected her when their mother went to prison and their mother's boyfriend committed a terrible act, ten-year-old Della tries to figure out what to do when her older sister attempts suicide.